2019
DOI: 10.1007/s12105-018-0986-3
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Keratosis, Contact Keratosis and Smokeless Tobacco Keratosis: Features of Reactive White Lesions of the Oral Mucosa

Abstract: White lesions of the oral cavity are quite common and can have a variety of etiologies, both benign and malignant. Although the vast majority of publications focus on leukoplakia and other potentially malignant lesions, most oral lesions that appear white are benign. This review will focus exclusively on reactive white oral lesions. Included in the discussion are frictional keratoses, irritant contact stomatitis, and smokeless tobacco keratoses. Leukoedema and hereditary genodermatoses that may enter in the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 35 publications
(58 reference statements)
1
53
0
10
Order By: Relevance
“…This presentation is mainly based on cellular changes, where white to gray appearance is mostly due to the increase in the thickness of the keratin layer and/or acanthosis with keratinocyte edema. Additionally, some types may cause an increase in the fibrous tissue composition of the connective tissue and collagen sclerosis ( Müller, 2019 ). Recent research has shown that various types of SLT harbor bacteria that can play a role in the carcinogenicity ( Halboub et al, 2020 , Monika et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This presentation is mainly based on cellular changes, where white to gray appearance is mostly due to the increase in the thickness of the keratin layer and/or acanthosis with keratinocyte edema. Additionally, some types may cause an increase in the fibrous tissue composition of the connective tissue and collagen sclerosis ( Müller, 2019 ). Recent research has shown that various types of SLT harbor bacteria that can play a role in the carcinogenicity ( Halboub et al, 2020 , Monika et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…• Tobacco pouch keratosis-this is a white patch found on the lower buccal grooves among smokeless tobacco users who retain their tobacco quid at the site (Müller, 2019). Most of them will resolve following discontinuation of the habit but those that persist should be included within the group leukoplakia.…”
Section: Skin Graft Known History Of a Skin Graftmentioning
confidence: 99%
“…The prevalence of frictional keratosis is difficult to assess as it can be easily mistaken with leukoplakia. Some reports suggest that it may appear in about 5% of the population [2]. After elimination of the possible mechanical irritation, the lesion should disappear within a period of 4-8 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Although OSCC may develop de novo, some of them originate from potentially malignant disorders (PMD) which commonly appear in the oral cavity as white lesions, such as oral leukoplakia and oral lichen planus (OLP). These conditions may cause diagnostic problems for clinicians, usually being miscategorized as other benign lesions, especially frictional keratosis [2]. It is advisable to perform a biopsy and confirm a provisional diagnosis for any persistent white lesion, especially if its clinical appearance is not specific [3].…”
Section: Introductionmentioning
confidence: 99%